Evaluation of symptoms of stress in university professors: quality of life in teaching - Helena de Ornellas Sivieri Pereira; Marcela Cunha do Amaral; Fabio Scorsolini-Comin (Universidade Estadual Paulista Júlio de Mesquita Filho, 2011)
The aim of this study was to evaluate the presence of stress symptoms in a sample of teachers from a private university in the state of Minas Gerais, Brazil. 147 teachers of different graduate courses in the areas of Humanities, Health, Education, Technology and Veterinary participated voluntarily of this study. The Stress Symptoms Inventory for Adults Lipp (SSI) was applied individually. The results indicated that 55.1% of teachers did not show symptoms of stress. Of the remainder (44.9%), stress is presented in moderate degree, with most in the resistance stage. The psychological symptoms appeared in greater percentage than the physical and in some cases associated with the physical. It is suggested further investigation to identify the stressors in teaching in higher education, with the prospect of developing programs for the alleviation of symptoms and thus promoting a better quality of life.